2005
DOI: 10.1001/archpedi.159.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attitudes About Sexually Transmitted Infection Vaccination for Their Adolescent Children

Abstract: Parents were accepting of the idea of vaccinating their adolescent children against STIs. The most salient issues were severity of infection and vaccine efficacy, not sexual transmissibility. Parents also favored vaccines for infections that had no method of behavioral prevention available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
125
4
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(141 citation statements)
references
References 30 publications
7
125
4
5
Order By: Relevance
“…Mothers have been shown to be highly involved in their children's healthcare decisions, especially with regards to HPV vaccination. [8][9][10][11][12] Less is understood about the role that fathers or pediatric patients play in this process. It has been observed that Hispanic and black fathers prefer to defer decisions about HPV vaccination to female caretakers or trusted friends, while female Hispanics often prefer to make these decisions collaboratively.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers have been shown to be highly involved in their children's healthcare decisions, especially with regards to HPV vaccination. [8][9][10][11][12] Less is understood about the role that fathers or pediatric patients play in this process. It has been observed that Hispanic and black fathers prefer to defer decisions about HPV vaccination to female caretakers or trusted friends, while female Hispanics often prefer to make these decisions collaboratively.…”
Section: Introductionmentioning
confidence: 99%
“…The most salient issues include high efficacy, safety, severity of infection, perceived risk, physician recommendation, and, for providers, professional society recommendation. Acceptability by parents and providers appears to be higher for older adolescents, although one study 138 found that age was not a factor for parents of adolescent children. Some parents expressed concern that a vaccine would increase unsafe sexual behavior, 118,119 while another study reported that sexual transmission did not affect parental attitudes.…”
Section: Hpv Vaccine Acceptabilitymentioning
confidence: 95%
“…Several small studies on HPV vaccine acceptability among young women, [134][135][136] parents of adolescents, 118,119,137,138 and providers 139,140 have suggested that overall acceptability for a prophylactic HPV vaccine is high. Multiple factors influenced attitudes.…”
Section: Hpv Vaccine Acceptabilitymentioning
confidence: 99%
“…Some believe this could promote conversations about sexual behavior that parents might be unwilling to have or be uncomfortable discussing [34][35][36]. Others think that talk about sex could encourage undesirable behavior, with some parents worrying that consent to have the vaccine could be taken as a warrant for early sexual activity [29][30][31][32][34][35][36].…”
Section: Consent For Vaccinationmentioning
confidence: 99%
“…Although some parents might worry that vaccination could promote risky sexual behavior, the majority of them concede that the benefits provided from the vaccine outweigh such risks [35][36][37]. Moreover, parents initially opposed to immunization change their minds in favor of allowing vaccination when they are given more information about the virus and its associated ills [38].…”
Section: Consent For Vaccinationmentioning
confidence: 99%